Theoretical Review of Weight Functions for Rigid Line Inclusions: Implications for Stress Singularities and Crack Propagation - Charitidis J. Panagiotis (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
A comprehensive theoretical analysis of weight functions for rigid line inclusions in elastic materials is presented. Classical fracture mechanics approaches were extended to accurately predict stress intensity factors (SIFs) at the tips of these inclusions, which are crucial for understanding material failure. The analysis covered both static and dynamic loading conditions, including transient Mode-III problems. Weight functions for various deformation modes were derived, and the impact of rigid line inclusions on stress singularities and crack propagation was explored. These insights are valuable for the design and analysis of composite structures and materials subjected to dynamic loading.